Does globalization lead to specialization? - Carsten Eckel (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2003)
The relationship between market integration and the degree of specialization plays a key role in many areas of economics. In contrast to previous studies, we illustrate that globalization does not necessarily lead to specialization. The analysis is conducted in an extended Dixit-Stiglitz- Ethier framework. Whether globalization leads to specialization or to more integrated production structures depends on characteristics of the cost function and on firm behavior. By comparing these changes to the optimal degree of specialization we show that globalization can reduce the efficiency of the industrial structure.
Keywords: F12; L11; L22; 330; Fragmentation; Specialization; Market Integration; Globalization; Vertical Equilibrium; Economies of Scale